Investigation into water-soluble perylene diimides for thin film formation - Weitzel, Corey R. (Kansas State University, 2008)
Three water-soluble perylene diimides (PDIs) were investigated to examine differences in their thin film forming properties. The PDI thin films investigated in this thesis are formed in an electrostatic-self-assembled (ESA) layer-by-layer (LBL) process by the use of a dip coater. The three PDIs employed are sodium bis (sulfonatopropyl) perylene diimide (PDISO[subscript]3[superscript]2-), bis (trimethylammonioethyl) perylene diimide diiodide (PDIDI[superscript]2+), and N-(butoxypropyl)-N'-(2-(N,N,N-trimethylammonio)-ethyl) perylene-3,4,9,10-tetracarboxylic diimide iodide (C[subscript]7OPDI[superscript]+). Thin films were made by alternately depositing the PDIs with counter polyelectrolyte (PEs). The PEs employed were poly(diallyldimethylammonium chloride) (PDDA[superscript]+) and poly(acrylic acid) (PA[superscript]-), depending on the charge of the PDI. PDIs were determined to be aggregated in all three PDI precursor solutions. The fraction of PDI aggregated in each was found to be 0.972, 0.903, and 0.993, for the PDISO[subscript]3[superscript]2-, PDIDI[superscript]2+, and C[subscript]7OPDI[superscript]+, respectively. The C[superscript]7OPDI[superscript]+ solution was the most aggregated only having one charge group, which makes it more hydrophobic. Thin films prepared from the solutions all displayed an absorbance spectrum similar to the aggregated form. All the composites displayed linear growth in film thickness and fiber width with bilayer number. However, the three composites gave unique surface morphologies. The PDISO[subscript]3[supercript]2-[dot in middle of line]PDDA+ composite was found to incorporate highly curled intertwined fibers compared to the PDIDI[superscript]2+[dot in middle of line]PA[superscript]- composite, where the fibers were not intertwined. The fiber structure was found to change after 15 bilayers. This change in morphology was attributed to the fibers grafting together and overlapping causing the loss of original fiber structure. The two symmetric composites differed in the film thickness with the PDISO[subscript]3[superscript]2-[dot in middle of line]PDDA[superscript]+ being thicker than the PDIDI[superscript]2+[dot in middle of line]PA[superscript]- composite. This was attributed to the molecular weights (MW) of the polyelectrolytes investigated during thin film deposition, with the PDDA[superscript]+ having a much higher MW. C[subscript]7OPDI[superscript]+[dot in middle of line]PA[superscript]- thin film composite had a film thickness approximately equal to the PDISO[subscript]3[superscript]2-[dot in middle of line]PDDA[superscript]+ composite, indicating precursor aggregation also influences deposition rate. The C[subscript]7OPDI[superscript]+[dot in middle of line]PA[superscript]- composite incorporated wavy thin fibers that appeared aligned in the dipping direction. This alignment was visible for bulk samples in UV-vis absorption dichroism studies. The alignment was parallel to the dipping direction of the substrate.
Keywords: Water-soluble perylene diimides; Thin film formation; Layer-by-layer; Electrostatic-self-assembly; Dip-coater; Organic semiconductor thin films formation; Chemistry, Polymer (0495)